BOOK REVIEWS (Journal of Finance, 1971)
Book reviewed in this article: Aggregate Theory and Policy: A Century of Pay . By E. H. P helps B rown with M argaret H. B rowne . Aggregate Theory and Policy: Targets and Indicators of Monetary Policy . Edited by K arl B runner . Aggregate Theory and Policy: Bankers' Diplomacy: Monetary Stabilization in the Twenties . By R ichard H. M eyer . Aggregate Theory and Policy: Industrial Market Structure and Economic Performance . By F rederic M. S cherer . Aggregate Theory and Policy: The Political Economy of Prosperity . By A rthur M. O kun . Aggregate Theory and Policy: Setting National Priorities: The 1971 Budget . By C harles L. S chultze with E dward K. H amilton and A llen S chick . Aggregate Theory and Policy: Economic Forecasting . By H erman O. S tekler . Business Finance and Investments: An Integrated Analysis For Managerial Finance . By M. C hapman F indlay , III, and E dward E. W illiams . Business Finance and Investments: Cases in Managerial Finance . By E ugene F. B righam , T imothy J. N antell , R obert T. A ubey , and S tephen L. H awk . Business Finance and Investments: The Predictability of Stock Market Prices . By C. W. J. G ranger and O. M orgenstern . Financial Institutions and Markets: Banking in the 1970's . By T he I nstitute of B ankers . Financial Institutions and Markets: Mutual Funds and Other Institutional Investors: A New Perspective . By I rwin F riend , M arshall B lume and J ean C rockett . Financial Institutions and Markets: Economic Factors in the Growth of Corporation Giving . By R alph L. N elson . International Finance: National Interests and the Multinational Enterprise . By J ack N. B ehrman . International Finance: The Joint Venture Process in International Business: India and Pakistan . By J ames W. C. T omlinson . International Finance: The Case Against Floating Exchanges . By P aul E inzig . International Finance: Forward Exchange and Internal‐External Equilibrium (Michigan International Business Studies Number 12), by J ay H. L evin . International Finance: The Technology Factor in International Trade . Edited by R aymond V ernon . Public Finance: Education, Income, and Human Capital . Edited by W. L ee H ansen . Public Finance: Psychological Approaches to the Study of Saving . By F olke O lander and C arl ‐M agnus S eipel . Public Finance: Halfway to Tax Reform . By J oseph A. R uskay and R ichard A. O sserman . Public Finance: Public Investment Planning in Civilian Nuclear Power . By J ohn M. V ernon .